A Study of Sympathetic Skin Response in persons with Type-2 Diabetes Mellitus - R, Ravindran; Iyer, Saraswati; Deshpande, Mangala (International Journal of Clinical and Biomedical Research, 2024)
Background: Impairment in Autonomic nervous system constitutes to one of the most serious and important complications in persons with Diabetes. Noninvasive Sympathetic Skin Response (SSR) test assesses the impairment of the sympathetic fibers of the peripheral nerves is widely used and valid markers of autonomic neuropathy. Considering the cost effectiveness of these tests, SSR testing would help us in understanding the prevalence of autonomic dysfunction in patients with Type 2 Diabetes Mellitus (T2DM). Method: 30 adults diagnosed with T2DM and 25 normal healthy adults who volunteered to participate were assessed for SSR in their foot and hand. SSR was assessed using Neurowerk EMG/NCV equipment capable of assessing SSR. Electrical current was used on the median nerve at the wrist to elicit SSR. Results: SSR was elicited in all participants. In persons with T2DM, mean SSR latency and SSR Amplitude for the hand were 1.587 ± 0.759 secs and 1499 ± 1411 microVolt respectively. The mean SSR Latency and SSR Amplitude for the foot were 2.478 ± 1.247 secs and 39.2 ± 901.07 micro Volts respectively. Characteristics of the SSR curves were discussed. Conclusion: In persons with T2DM, mean SSR latency of hand and foot were 1.587 ± 0.759 and 2.478 ± 1.247 seconds respectively. Mean SSR amplitude of hand and foot were 1499 ± 1411 and 939.2 ± 901.07 microVolts respectively. Mean values SSR Latency & Amplitude of persons with T2DM were significantly different from that of normal healthy adult. Keywords: Sympathetic Skin Response, Automonic dysfunction, Diabetes mellitus.